2018
DOI: 10.1002/chem.201801278
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Metal–N‐Heterocyclic Carbene Complexes to Control Reactivity in Catalytic Reactions

Abstract: Confinement of a metal complex is a promising way to induce reactivity modulation and selectivity. Combining this principle with the properties of N-heterocyclic carbenes (NHC) used as ligands is therefore of great interest. NHCs metal complexes have been encapsulated in polymeric structures (metal-organic frameworks, metal organic polymers and porous organic polymers), and in molecular containers (capsules, cages or cavitands). This confinement induced reactivity change, on and off switching of reactions, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…NHC‐Au catalysts provide relevant points to consider, as their catalytic activity drastically changes inside the hexamer . These themes have been more carefully elaborated on in a series of recent reviews …”
Section: Introductionmentioning
confidence: 99%
“…NHC‐Au catalysts provide relevant points to consider, as their catalytic activity drastically changes inside the hexamer . These themes have been more carefully elaborated on in a series of recent reviews …”
Section: Introductionmentioning
confidence: 99%
“…Up to 50 % ee was achieved for the enantioselectivec ycloisomerization of N-allyl-4-methyl-N-(3-phenylprop-2-yn-1-yl)benzenesulfonamide.Confining cavity-shaped ligands are increasingly popular in catalysis because of their capacity to controlt he first coordination sphere of metals and in doing so produce unusual selectivities during metal-catalyzed reactions. [1] However,t heir use in asymmetric catalysis remains scarce due to the lack of suitable chiral macrocyclicr eceptors. [2] Amongst them, the naturally-occurring cyclodextrins (CDs) [3] occupy ap lace of choice as they are cheap, enantiopure, available in different sizes, and can be easily derivatized at specific locations.S of ar,m ost efforth as concentrated on asymmetric catalytic reactions taking place in water to take advantage of the host-guest properties of CDs in this medium.…”
mentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2020 RSC Adv., 2020, 10, 39323-39327 | 39325 À anions can also be encapsulated inside the cavity. With the addition of KBF 4 to Pd 6 L 12 ,19 F NMR shows two signals, one strong signal at À148.27 ppm corresponding well with the peak of free BF 4 À in DMSO-d 6 (À148.3 ppm), and the other new signal at À144.1 ppm (Fig. S20and S21 †) 11.…”
mentioning
confidence: 84%
“…13,14 Discrete assemblies based on NHC ligands including molecular metallocycles and cages have received increasing attention [15][16][17][18] because they may induce reactivity change, selectivity and product distribution variation. 19,20 However, few molecular cages with well-dened cavities are reported in the literature. [21][22][23] Remarkably, Nitschke et al reported M 4 L 6 (M ¼ Zn(II), Cd(II)) cages with Au(I)-NHCbased ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation